High Flow Nasal Cannula Decreased Pulmonary Complications in Neurologically Critically Ill Patients - Wang, Shuanglin; Yang, Jingjing; Xu, Yanli; Yin, Huayun; Yang, Bing; Zhao, Yingying; Wei, Zheng Zachory; Zhang, Peng (Frontiers in Human Neuroscience, 2022)
Objective: Pulmonary complications badly affect the recovery of the neurological function and the neurological prognosis of neurological critically-ill patients. This study evaluated the effect of high-flow nasal cannula (HFNC) therapy on decreasing pulmonary complications in neurologically critically-ill patients. Patients and Methods: The patients admitted to the intensive care unit (ICU) with serious neurological disease and receiving oxygen therapy were retrospectively reviewed. Patients divided into the HFNC group and the COT (conventional oxygen therapy) group. The patients’ baseline data, short-term outcomes of respiratory complications and general outcomes including hospital stay, ICU stay and mortality, and neurological function were compared between the two groups. Multiple logistic regression analyses were performed to analyze the occurrence of pneumonia, sputum viscosity, mechanical ventilation rate, length of hospitalization and length of stay in ICU, to analyze the influencing factors. Results: 283 patients were enrolled in this study, including 164 cases in the HFNC group and 119 cases in the COT group. Compared with the conventional oxygen therapy group, the HFNC group had remarkably less mechanical ventilation requirement, with lower phlegm viscosity. ICU stay and total hospital stay were significantly shorter in the HNFC group. Conclusion: HFNC seemed to decrease pulmonary complications in neurologically critically-ill patients and improve recovery of neurological function and neurological prognosis. But it still needs further studies.